Aspectos geológicos y geodinámicos de flujos aluvionales en la quebrada Jicamarca y análisis de la vulnerabilidad para la implementación de un Sistema de Alerta Temprana (SAT) en el centro poblado Cajamarquilla - Chiroque, Cristhian (2016)
The alluvial flows study occurred in the Jicamarca gorge was made in order to design and implement an Early Warning System (SAT), considering geological mapping and geodynamic of the deposits and materials found on the alluvial terraces and alluvial fans originated by ancient flows occurred in the Colca, El Silencio, Río Seco, Huaycoloro and Jicamarca gorge through these, types of flows were determined. This is a descriptive study of the physical characteristics of the rocks (source of supply of materials for future alluvium) outcropping along the tributaries that form the Jicamarca gorge. The delimitation of geoforms as 22 alluvial fans and the total approximate volume of contributors materials along the basin (1,974,522 m3) was calculated. The results of field and laboratory work conducted over one year, show that the Colca, El Silencio and Río Seco gorge contribute whith materials in 25%, 5% and 70% respectively. Described above determines that there are conditions that going to continue flows that may affect the security of towns located in the lower part of the basin, one of the most affected is the Cajamarquilla town. That is why, estimating the vulnerability of the 9 urban sectors that make up the town was made, taking into account the Manual para la evaluación de riesgos of CENEPRED, and it was determined that the social, economic and environmental vulnerability of the area study is medium, high and very high respectively.